THE EFFECTIVENESS OF THE DISCOVERY LEARNING STRATEGY IN SOCIAL SCIENCE CLASSES AT MTS NUR HADI MUARA JAWA - Frista Iin Wahyuni (English Study Program University of Pasir Pengaraian, 2025)
This study aims to examine the effectiveness of the Discovery Learning strategy in improving students’ learning outcomes in Social Science classes at MTs Nur Hadi Muara Jawa. A quantitative approach with a quasi-experimental design was employed, involving an experimental group taught using Discovery Learning and a control group taught using conventional instructional methods. The population consisted of all Social Science students at MTs Nur Hadi Muara Jawa, with two classes selected as research samples through purposive sampling. Data were collected using achievement tests and classroom observation instruments. The results revealed that students in the experimental group achieved higher post-test scores and demonstrated greater classroom engagement compared to those in the control group. Statistical analysis indicated a significant difference in learning outcomes between the two groups. These findings suggest that Discovery Learning is an effective instructional strategy for enhancing both cognitive achievement and active participation in Social Science learning. The study recommends the implementation of Discovery Learning to promote student-centered learning in madrasah contexts and encourages further research involving broader samples and additional learning variables.